Transverse relaxation‐based assessment of mammographic density and breast tissue composition by single‐sided portable NMR. Issue 3 (29th April 2019) - Ali, Tonima S.; Tourell, Monique C.; Hugo, Honor J.; Pyke, Chris; Yang, Samuel; Lloyd, Thomas; Thompson, Erik W.; Momot, Konstantin I.
Abstract : Purpose: Elevated mammographic density (MD) is an independent risk factor for breast cancer (BC) as well as a source of masking in X‐ray mammography. High‐frequency longitudinal monitoring of MD could also be beneficial in hormonal BC prevention, where early MD changes herald the treatment's success. We present a novel approach to quantification of MD in breast tissue using single‐sided portable NMR. Its development was motivated by the low cost of portable‐NMR instrumentation, the suitability for measurements in vivo, and the absence of ionizing radiation. Methods: Five breast slices were obtained from three patients undergoing prophylactic mastectomy or breast reduction surgery. Carr‐Purcell‐Meiboom‐Gill (CPMG) relaxation curves were measured from (1) regions of high and low MD (HMD and LMD, respectively) in the full breast slices; (2) the same regions excised from the full slices; and (3) excised samples after H2 O‐D2 O replacement. T 2 distributions were reconstructed from the CPMG decays using inverse Laplace transform. Results: Two major peaks, identified as fat and water, were consistently observed in the T 2 distributions of HMD regions. The LMD T 2 distributions were dominated by the fat peak. The relative areas of the two peaks exhibited statistically significant ( P < .005) differences between HMD and LMD regions, enabling their classification as HMD or LMD. The relative‐area distributions exhibited no statistically significant differences between full slices and excised samples. Conclusion: T 2 ‐based portable‐NMR analysis is a novel approach to MD quantification. The ability to quantify tissue composition, combined with the low cost of instrumentation, make this approach promising for clinical applications.